Development of combined microstructure and structure characterization facility for in situ and operando studies at the Advanced Photon Source. Issue 3 (5th June 2018) - Ilavsky, Jan; Zhang, Fan; Andrews, Ross N.; Kuzmenko, Ivan; Jemian, Pete R.; Levine, Lyle E.; Allen, Andrew J.
Abstract : The ultra‐small‐angle X‐ray scattering (USAXS) facility at the Advanced Photon Source has been significantly upgraded to provide rapid USAXS scanning at high X‐ray energies together with associated pinhole small‐angle X‐ray scattering (SAXS) and wide‐angle X‐ray scattering (WAXS) measurements. Complete USAXS/SAXS/WAXS data can be obtained within 5 min, allowing flexible in situ and operando measurement capabilities under a wide range of conditions. Abstract : Following many years of evolutionary development, first at the National Synchrotron Light Source, Brookhaven National Laboratory, and then at the Advanced Photon Source (APS), Argonne National Laboratory, the APS ultra‐small‐angle X‐ray scattering (USAXS) facility has been transformed by several new developments. These comprise a conversion to higher‐order crystal optics and higher X‐ray energies as the standard operating mode, rapid fly scan measurements also as a standard operational mode, automated contiguous pinhole small‐angle X‐ray scattering (SAXS) measurements at intermediate scattering vectors, and associated rapid wide‐angle X‐ray scattering (WAXS) measurements for X‐ray diffraction without disturbing the sample geometry. With each mode using the USAXS incident beam optics upstream of the sample, USAXS/SAXS/WAXS measurements can now be made within 5 min, allowing in situ and operando measurement capabilities with great flexibility under a wide range of sample conditions. These developments are described, together with examples of their application to investigate materials phenomena of technological importance. Developments of two novel USAXS applications, USAXS‐based X‐ray photon correlation spectroscopy and USAXS imaging, are also briefly reviewed.